EXPLORING THE IMPACT OF CELEBRITY ENDORSEMENT AND BRAND AWARENESS ON CONSUMER BEHAVIOR: A CASE STUDY OF ES TEH INDONESIA IN KOTA BARU JAMBI - Sabrina, Hanan Laras; Fahdillah, Yosi; Pangestu, Mira Gustiana (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This For entrepreneurs, the internet is useful for promoting their business to consumers. The development of digital technology and the growth of the business world in the current era is increasingly heading towards a global direction which makes a company required to establish the right marketing strategy in order to win marketing and be able to compete competitively with competitors. The purpose of this study was to determine the effect of celebrity endorsement and brand awareness on purchasing decisions for Indonesian iced tea, Kota Baru Jambi branch. The population of this study were consumers of Indonesian iced tea, Kota Baru Jambi branch with a sample size of 100 respondents using the lameshow formula. The sampling technique used purposive sampling technique using several criteria. This study uses quantitative methods and the data source used is primary data and data collection using a questionnaire distributed via google form. While the scale in this study uses a Likert scale. The data processing method uses multiple linear regression analysis, determination coefficient, partial t test and simultaneous F test. The results showed that celebrity endorsement had a significant positive effect on purchasing decisions at the Indonesian iced tea branch of the new city of Jambi.Brand awareness has a significant positive effect on purchasing decisions at the Indonesian iced tea branch of the new city of Jambi. And simultaneously celebrity endorsement and brand awareness have an effect on purchasing decisions on Indonesian iced tea in the new city branch of Jambi.